Centralising and optimising decentralised stroke care systems: a simulation study on short-term costs and effects. Issue 1 (December 2017) - Lahr, Maarten; van der Zee, Durk-Jouke; Luijckx, Gert-Jan; Vroomen, Patrick; Buskens, Erik
Abstract Background Centralisation of thrombolysis may offer substantial benefits. The aim of this study was to assess short term costs and effects of centralisation of thrombolysis and optimised care in a decentralised system. Methods Using simulation modelling, three scenarios to improve decentralised settings in the North of Netherlands were compared from the perspective of the policy maker and compared to current decentralised care: (1) improving stroke care at nine separate hospitals, (2) centralising and improving thrombolysis treatment to four, and (3) two hospitals. Outcomes were annual mean and incremental costs per patient up to the treatment with thrombolysis, incremental cost-effectiveness ratio (iCER) per 1% increase in thrombolysis rate, and the proportion treated with thrombolysis. Results Compared to current decentralised care, improving stroke care at individual community hospitals led to mean annual costs per patient of $US 1, 834 (95% CI, 1, 823–1, 843) whereas centralising to four and two hospitals led to $US 1, 462 (95% CI, 1, 451–1, 473) and $US 1, 317 (95% CI, 1, 306–1, 328), respectively (P  < 0.001). The iCER of improving community hospitals was $US 113 (95% CI, 91–150) and $US 71 (95% CI, 59–94), $US 56 (95% CI, 44–74) when centralising to four and two hospitals, respectively. Thrombolysis rates decreased from 22.4 to 21.8% and 21.2% (P  = 0.120 andP  = 0.001) in case of increasing centralisation. Conclusions Centralising thrombolysis substantially lowers mean annual costs per patient compared to raising stroke care at community hospitals simultaneously. Small, but negative effects on thrombolysis rates may be expected.